1997
DOI: 10.1038/sj.ijo.0800502
|View full text |Cite
|
Sign up to set email alerts
|

The non-genetic determinants of central adiposity*

Abstract: Central adiposity carries an increased risk of non-insulin dependent diabetes mellitus (NIDDM), cardiac disease, hypertension and death, and is closely related to insulin resistance. Genetic factors explain a large proportion of the population variance in central adiposity, although the genotypic characteristics remain obscure. Hormonal factors such as endogenous sex steroid levels, the menopause, hormone replacement therapy and cortisol may in¯uence body fat partitioning. The link between dietary factors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1
2

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 48 publications
0
24
1
2
Order By: Relevance
“…This finding, together with the larger WC of the men in the high-fat, low-carbohydrate diet group, is consistent with the results of prospective studies showing that high dietary fibre levels are associated with a reduction in the risk of coronary heart disease. 54,55 The complex nature of the relationships between alcohol consumption and body weight or fat distribution is suggested by the conflicting findings of observational studies: 56,16 generally, an inverse association between BMI and alcohol intake has been reported for women, and a slight positive relationship for men. [57][58][59][60] It is not known why male drinkers are no heavier than abstainers, or why alcohol may even promote leanness in women, 61,62,50 although it has been suggested that the calories from alcohol are added to energy intakes from other sources in men, and that the energy from alcohol intake displaces sucrose in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding, together with the larger WC of the men in the high-fat, low-carbohydrate diet group, is consistent with the results of prospective studies showing that high dietary fibre levels are associated with a reduction in the risk of coronary heart disease. 54,55 The complex nature of the relationships between alcohol consumption and body weight or fat distribution is suggested by the conflicting findings of observational studies: 56,16 generally, an inverse association between BMI and alcohol intake has been reported for women, and a slight positive relationship for men. [57][58][59][60] It is not known why male drinkers are no heavier than abstainers, or why alcohol may even promote leanness in women, 61,62,50 although it has been suggested that the calories from alcohol are added to energy intakes from other sources in men, and that the energy from alcohol intake displaces sucrose in women.…”
Section: Discussionmentioning
confidence: 99%
“…14 Furthermore, the inconsistent findings of studies of the relationship between physical activity and BMI-assessed obesity have been partly attributed to the confounding effect of muscle mass, 15 and so also the contradictory results of studies investigating the influence of behavioural factors (particularly, alcohol consumption) on central adiposity as measured using the waist-hip ratio (WHR), which is affected by both intra-abdominal fat and gluteal muscle mass. 16 It is now well known that both body composition (lean and fat mass) and body fat distribution (the body shape) play a major role in causing morbidity and mortality. [17][18][19][20][21][22][23][24][25] In particular, lower levels of muscle mass and subcutaneous fat are associated with an increased risk of cancer mortality; 26 excess intra-abdominal fat, as measured by large waist circumference (WC), is associated with an increased risk of developing a number of chronic diseases (including type 2 diabetes and cardiovascular disease), 27,28 whereas larger hip circumference (HC) independently predicts good health and is associated with a better metabolic profile.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction may be genuine, since smoking tends to be associated with reduced body weight (Grunberg, 1990) (but not necessarily central adiposity, (Samaras & Campbell, 1997), and it may potentially modify (and obscure) the effect of beer on obesity. However, we remain cautious on this issue because we tested for several interactions in this relative small data set, and the results may be because of type I error.…”
Section: Discussionmentioning
confidence: 99%
“…26 It has been suggested that abdominal fat is more responsive to exercise than fat in other parts of the body. 3 Exercise-induced alterations in lipolytic activity are shown to be greater in abdominal than in gluteofemolar adipocytes, and therefore abdominal fat is more readily mobilized during exercise than are peripheral depots. 3 Evidence from randomized controlled trials also suggests that exercise-induced weight loss is associated with reductions in abdominal obesity, 26 and that exercise alone, even without weight loss, reduces abdominal fat.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, the major health risks of obesity are related more to the abdominal distribution of body fat than to its total amount. 3 Overall obesity is typically measured by the body mass index (BMI), which describes body weight in relation to body height, and abdominal obesity is typically measured by waist circumference (WC). Both BMI and WC are widely used in large epidemiological studies as indicators of obesity.…”
Section: Introductionmentioning
confidence: 99%